(untitled) (Bangladesh Pharmaceutical Journal, 2013)
The present study was conducted to investigate the solubilising capacity of polyvinylpyrrollidone (PVP K-30), Polyethylene glycol (PEG 6000), Polysorbate (Tween 80) and Sodium lauryl sulphate (SLS) for paracetamol. In our study, PVP K-30 exhibited 5 times, Tween 80 showed 3 times and SLS displayed 2 times higher solubilising capacity than water. Here, PVP K-30 exhibited the highest solubilising capacity and the value was 6.36 ± 0.063 (mg /ml), whilst PEG 6000 in the same study failed to show any significant increase (p> 0.05, unpaired t-test, two-tailed). DOI: http://dx.doi.org/10.3329/bpj.v16i1.14498 Bangladesh Pharmaceutical Journal 16(1): 77-80, 2013